Structural and dynamic characterization of two-component waterproof mortars by 1H NMR, FT-IR, mechanical and SEM investigations. (16th May 2023) - Cadar, Daniel; Manea, Daniela Lucia; Jumate, Elena; Popa, Florin; Moldovan, Dumitrița; Fechete, Radu
Highlights: Pores' structure and distribution of two component latex-based waterproof mortars. Correlation between SEM, FT-IR, mechanical, NMR measurements of 4 types of mortars. Small amount of 1 H found in large pores supports the waterproofing properties. Modification in pore size and structure monitored for 28 days by T 2 -distributions. Advanced characterization of mortars hydration by 2D 1 H NMR T 1 - T 2 correlation map. Abstract: Advanced 1 H NMR relaxometry is an important tool used for the characterization of a large range of materials like mortars. CPMG pulse sequence and saturation recovery methods were used for the measurement of four samples (MF, C166, P288, AQSE) of two-component waterproof mortars at 1, 3, 7, and 28 days after preparation. In general, four dynamics components were observed for the T 2 Laplace distributions can be associated with 1 H from bound water and with those from small, medium, and large pores. Due to particular characteristics, such as high elasticity the flexural tensile strength and compressive strength could not be measured for all samples. SEM images were recorded, and the reported composition was correlated to NMR parameters and FT-IR spectra. The hydrating behaviour of the two-component waterproofing mortar dried under natural conditions was observed for 28 days and then the hydration process was characterized using 2D 1 H NMR T 1 - T 2 correlation map.